English Language Teaching Praxes and Policies in Indonesia: A Critical Review - Lailatul Maya; Ifan Iskandar (Proceedings International Conference on Teaching and Education (ICoTE), 2022)
This study aimed to expose English language teaching practices and policies in Indonesia. This study employed a qualitative approach in the form of document analysis. Analyses were conducted on books, research papers, national policies, and curricular documents. From the inaugural curriculum in 1947 to the present curriculum in 2013, the Indonesian government has provided financing for English language teaching. In contrast, the 2013 curriculum gives less time to the teaching of the English language than earlier editions. From the perspective of training all Indonesians to become global citizens, language proficiency is required. Therefore, both teachers and students must have language competency. However, English language teaching as the main lesson at primary school levels is no longer compatible with current Indonesian educational policy. Hence, English is supposed to be taught in all school level with the goal of fostering global citizens with language proficiency, since being a global citizen in the age of globalization is inevitable.